MEDICAL AND SOCIAL ASSISTANCE TO CHILDREN BORN TO HIV-POSITIVE WOMEN AND LEFT WITHOUT PARENTAL CARE - V. N. Timchenko; Yu. A. Arkhipovа; N. D. Dzhangavadze (Детские инфекции (Москва))
The article presents information about the ways of rendering of the medical-social assistance to children born to HIV-positive women. The results of clinical examination of children living in the specialized orphanage are cited for years 2000—2012. Authors have analyzed the peculiarities of the social structure, ways of living arrangement and the health of children left without parental care.